Eolian depositional phases during the past 50 ka and inferred climate variability for the Pampean Sand Sea, western Pampas, Argentina. (1st May 2016) - Tripaldi, Alfonsina; Forman, Steven L.
Abstract: The Pampean Sand Sea, which occurs from the Argentinian Pampas to the eastern Andean piedmont, hosts presently stabilized dune fields spanning the late Quaternary. This study integrates previous results and presents new geomorphic, stratigraphic, sedimentological, and chronologic data for nineteen >2 m-thick eolian successions for the San Luis paleo-dune field, western Pampas, to better constrain the depositional history. Six eolian depositional phases are identified spanning the past 50 ka, interposed with paleosols and/or bounded by erosive surfaces. Age control was from 61 OSL ages of small aliquots of quartz grains from eolian stratigraphic units. The inferred timing of eolian phases are at ca. 70 ± 10 yr, 190 ± 20 yr, 12 to 1 ka, 22 to 17 ka, 29 to 24 ka, and 40 to 32 ka. A maximum span for periods of pedogenesis at ca. 12 to 17 ka, 22 to 24 ka, and 29 to 32 ka was provided by bounding OSL ages, which broadly overlap with high stands of pluvial lakes and glacier advances in the central Andes. We infer that the added precipitation may reflect expansion of the Southern Hemisphere monsoon, associated with Northern Hemisphere Heinrich events, leading to episodes of significantly wetter conditions (>350 mm MAP) to at least 35° S. Most of the Holocene (12 ka to 0.8 ka) was characterized by sand sheet deposit under drier than present conditions (100–450 mm MAP), associated with Monte-type vegetation (shrub steppe). The latest two eolian depositional phases, occurred at ca. 190 and 70 yr ago, during the historic period with European settlement and are related to anthropogenic landscape disturbance, though the youngest phase was concomitant with 1930s drought. Wet conditions dominated since ca. AD 1970 with new lakes and rivers forming across this eolian terrain; an incongruous environmental response in reference to drier conditions for most of the Holocene. Highlights: Eolian deposits spanning the past 50 ka are ubiquitous in western Pampas, Argentina. Sedimentary units bounded by paleosols or unconformities indicate six eolian depositional events. OSL ages dated eolian activity at ca. 70 ± 10 yr, 190 ± 20 yr, 12–1 ka, 22–17 ka, 29–24 ka and 40–32 ka. Periods of pedogenesis broadly overlap at paleo-lake highstands and glacier advances at central Andes. Pedogenesis reflects wetter intervals related to increased monsoonal rainfall and Heinrich events.